MENINGKATKAN KEMAMPUAN BERBICARA BAHASA JEPANG MELALUI VIDEO PRESENTASI DESTINASI WISATA - Sri Muryati; Bekti Setio Astuti (Universitas Pendidikan Ganesha, 2024)
Speaking proficiency is a crucial aspect of language learning, particularly in foreign languages like Japanese. However, both teachers and learners face numerous challenges in enhancing this skill. This research aims to examine the use of video presentations in improving Japanese language learners' speaking abilities. The problems encountered include a lack of interest, difficulties in objectively assessing progress, and challenges in devising effective methods and materials. On the learners' side, challenges include low self-confidence, public speaking anxiety, limited vocabulary, and difficulties in expressing ideas clearly. The methodology employed in this study is a mix of quantitative and qualitative methods. Data were collected through feedback, teacher evaluations, and interviews with fourth-semester students of the Japanese Language D-3 Program at UNTAG Semarang.The research findings indicate that the use of video presentations is effective in enhancing students' speaking abilities. Students reported increased confidence and speaking skills after using video presentations. They also demonstrated improvements in organizing ideas, selecting appropriate vocabulary, and delivering information clearly and coherently. Students generally responded positively to the use of these presentation tasks. Evaluations also showed that video presentations provide relevant and beneficial contexts for developing Japanese language skills, including vocabulary expansion, pronunciation, and fluency. In conclusion, the use of video presentations in Japanese language learning is effective in improving students' speaking abilities. Recommendations can be made to further develop and refine this method in a broader learning context. Keywords : Video presentation, video, speaking skills, Japanese. Abstrak Kemampuan berbicara adalah aspek penting dalam pembelajaran bahasa, terutama bahasa asing seperti bahasa Jepang. Namun, banyak tantangan yang dihadapi baik oleh pengajar maupun pembelajar dalam meningkatkan kemampuan berbicara ini. Penelitian ini bertujuan untuk mengkaji penggunaan video presentasi dalam meningkatkan kemampuan berbicara mahasiswa bahasa Jepang. Permasalahan yang dihadapi adalah kurangnya minat, kesulitan menilai kemajuan secara objektif, dan kesulitan menyusun metode dan materi yang efektif. Di sisi pembelajar, tantangan meliputi kurangnya percaya diri, kecemasan berbicara di depan umum, keterbatasan kosakata, dan kesulitan menyampaikan ide dengan jelas. Metode yang digunakan dalam penelitian ini adalah mix method, yaitu campuran antara kuantitatif dan kualitatif. Data dikumpulkan melalui umpan balik, evaluasi pengajar, dan wawancara terhadap mahasiswa semester empat Program Studi D-3 Bahasa Jepang di UNTAG Semarang. Hasil penelitian menunjukkan bahwa penggunaan video presentasi efektif dalam meningkatkan kemampuan berbicara mahasiswa. Mahasiswa melaporkan peningkatan percaya diri dan keterampilan berbicara setelah menggunakan video presentasi. Mereka juga menunjukkan peningkatan dalam mengorganisir ide, memilih kosakata yang tepat, dan menyampaikan informasi dengan jelas dan terstruktur. Respon mahasiswa terhadap penggunaan tugas presentasi ini secara umum positif. Evaluasi juga menunjukkan bahwa video presentasi memberikan konteks yang relevan dan bermanfaat dalam mengembangkan kemampuan bahasa Jepang, termasuk penambahan kosakata, pengucapan, dan kelancaran berbicara. Kesimpulannya, penggunaan video presentasi dalam pembelajaran bahasa Jepang efektif dalam meningkatkan kemampuan berbicara mahasiswa. Rekomendasi dapat diberikan untuk terus mengembangkan dan memperbaiki metode ini dalam konteks pembelajaran yang lebih luas.